2009
DOI: 10.1016/j.yexcr.2009.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen inhibits RANKL-stimulated osteoclastic differentiation of human monocytes through estrogen and RANKL-regulated interaction of estrogen receptor-α with BCAR1 and Traf6

Abstract: The effects of estrogen on osteoclast survival and differentiation were studied using CD14-selected mononuclear osteoclast precursors from peripheral blood. Estradiol at ~1 nM reduced RANKLdependent osteoclast differentiation by 40-50%. Osteoclast differentiation was suppressed 14 days after addition of RANKL even when estradiol was withdrawn after 18 hours. In CD14+ cells apoptosis was rare and was not augmented by RANKL or by 17-β-estradiol. Estrogen receptor-α (ERα) expression was strongly down-regulated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 71 publications
2
92
1
1
Order By: Relevance
“…We showed in earlier studies that the FSHR isoform that is predominantly expressed in osteoclasts has a slightly smaller size than the ovarian form, consistent with deletion of an exon, probably exon 9 [3]. To address this hypothesis in sufficient detail to produce definitive results, we made new preparations from peripheral blood mononuclear cells (PBMCs), and using a purified (98%+) CD14+ fraction [15] from human blood obtained by procedures approved by the Institutional Review Board. Both PBMC and CD14+ cells were induced to form osteoclasts by incubation for up to 14 days with RANK-L, as in murine preparations, except that human-specific cytokines were used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed in earlier studies that the FSHR isoform that is predominantly expressed in osteoclasts has a slightly smaller size than the ovarian form, consistent with deletion of an exon, probably exon 9 [3]. To address this hypothesis in sufficient detail to produce definitive results, we made new preparations from peripheral blood mononuclear cells (PBMCs), and using a purified (98%+) CD14+ fraction [15] from human blood obtained by procedures approved by the Institutional Review Board. Both PBMC and CD14+ cells were induced to form osteoclasts by incubation for up to 14 days with RANK-L, as in murine preparations, except that human-specific cytokines were used.…”
Section: Resultsmentioning
confidence: 99%
“…The products of these two sequential amplification procedures showed that the FSHR type 2 isoform was present in PMBCs, CD14+ cells, osteoclasts prepared from CD14 cells, and ovarian control (COV) cells. A weak band was seen in CD14-negative cells, the fall-through from magnetic bead isolation of CD14+ cells [15]. This might represent type 2 FSHR in other white blood cells, but some CD14+ cells might not be captured by the magnetic beads.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TRAP activity at day 14 was indistinguishable between the two groups (Figure 4d). 29 Expression of mRNAs for TRAP (Acp5 gene), cathepsin K (Ctsk), and RANK (Tnfrsf11a), key osteoclast features, were not significantly different in WT and apoA-1 KO mice (Figure 4e). In aggregate these data show that apoA-1 deficiency suppresses differentiation of bone-forming osteoblasts, but has no significant effect on differentiation of bone resorbing osteoclasts.…”
Section: Hdl Receptor Effects Acth and Cortisol Productionmentioning
confidence: 97%
“…Indeed, transgenic males seem to exhibit almost no long bone phenotype, whereas females have a slightly more marked phenotype. Those differences can be explained by estrogenic osteoclast modulation [6]. This study will have to be completed by analyzes of jaw bone, in order to find if this RANK over-expression has different effects on different types of bone.…”
Section: Resultsmentioning
confidence: 99%